2018
DOI: 10.1136/jnnp-2017-317378
|View full text |Cite
|
Sign up to set email alerts
|

Functional neurological disorders in Parkinson disease

Abstract: A subtype of PD with functional neurological features is familial in one-fourth of cases and associated with more psychiatric than motor disability and greater use of diagnostic and healthcare resources than those without functional features. Functional manifestations may be prodromal to PD in one-third of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
93
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 16 publications
3
93
1
3
Order By: Relevance
“…Indeed, postencephalitic parkinsonism was the first and unexpected evidence that SFD‐related manifestations were rooted in a pathologically confirmed disease and not the mere result of psychodynamic processes. Today, high scores for SFD‐related items within several neuropsychological scales are found in 29%–67% of PD patients . We suggest that SFD symptoms, identified by neuropsychological scales and described as transient and tolerable phenomena, can be considered equivalent to early simple hallucinations.…”
Section: Somatic Symptom and Functional Disordersmentioning
confidence: 88%
See 4 more Smart Citations
“…Indeed, postencephalitic parkinsonism was the first and unexpected evidence that SFD‐related manifestations were rooted in a pathologically confirmed disease and not the mere result of psychodynamic processes. Today, high scores for SFD‐related items within several neuropsychological scales are found in 29%–67% of PD patients . We suggest that SFD symptoms, identified by neuropsychological scales and described as transient and tolerable phenomena, can be considered equivalent to early simple hallucinations.…”
Section: Somatic Symptom and Functional Disordersmentioning
confidence: 88%
“…The presence of PD‐DLB‐related SFDs was first reconsidered by a systematic study, confirmed by others, which showed that SFDs: (1) might precede or go along for several years with the appearance of motor and nonmotor features of the disease; (2) may also have a variable pattern of presentation; (3) may occur with far higher incidence in PD and DLB compared with other neurodegenerative disorders associated with parkinsonism and/or dementia; or (4) may correlate with and predict onset of cognitive decline …”
Section: Somatic Symptom and Functional Disordersmentioning
confidence: 99%
See 3 more Smart Citations